Christianity and criminal law - Hill, Mark 1965-; Doe, Norman; Helmholz, R. H.; Witte, John 1959- (Law and religion, 2020)
"This collection, by leading legal scholars, judges and practitioners, together with theologians and church historians, presents historical, theological, philosophical, and legal perspectives on Christianity and Criminal Law. Following an Introduction by Lord Judge, formerly Lord Chief Justice of England and Wales, the book is divided into four thematic sections. Part I addresses the Historical Contributions of Christianity to Criminal Law drawing on biblical sources, early church fathers and canonists, as far as the Enlightenment. Part II, titled Christianity and the Principles of Criminal Law, compares crime and sin, examines concepts of mens rea and intention, and considers the virtue of due process within criminal justice. Part III looks at Christianity and Criminal Offences, considering the Christian origins and continuing relevance for several basic crimes that every legal system prohibits. Finally, in Part IV, the authors consider Christianity and the Enforcement of Criminal Law, looking at defences, punishment, and forgiveness"--